An Experience of Peer Education Model among Medical Science University Students in Iran - N Peykari; F Ramezani Tehrani; H Malekafzali; Z Hashemi; Sh Djalalinia (Iranian Journal of Public Health, 2011)
Background: The purpose of this study was to evaluate the effectiveness of peer education among university students for reproductive health promotion based on researchers' experiences. Methods: This interventional study was conducted in Qazvin University of Medical Science during 2002 to 2004 through stakeholders' partnership and selection of 24 volunteer students according to their knowledge, interest, communication skills. Capacity building was performed through holding an interactive reproductive health coarse contained marital health, illegal abortion, family planning, STI/AIDS, communication and counseling skills. Trained peer educators have introduced to other student and present education and counseling formally and informally. A post interventional study was conducted after 9 months in order to find its effectiveness. Results: In our experience Stakeholders' partnership in community interventional programs led to the best expected availability of better health through ownership and adopting policies. In present study, the proper determined criteria for selection of peer educators and clear understood expectations of the peer educators' role were very important in health promotional program. Although peer education was acceptable program for university students, more support and supervising for peer groups are needed. The students believed that the power point of peer education and counseling related to same age groups sympathy, confident, well behaved, cheerful, and kind-hearted and peer educators awareness. Conclusion: Universities are appropriate real world for experience a friendly youth program and then disseminate it to other young communities. There seems peer education is effective strategy for reproductive health promotion and reinforce positive behaviors in youth.